Analisis Faktor-Faktor yang Mempengaruhi Pengangguran di Provinsi Banten 2015-2019 - Diaz Danindra, Muhammad; Triwahyunigtyas, Nunuk; Arrafi Juliannisa, Indri (CV. Publikasi Indonesia, 2022)
The problem of unemployment is a problem that always exists in the economic development process of a developing country, including Indonesia. One of the biggest contributors to the unemployment rate in Indonesia is Banten Province which has the highest number of unemployed during 2015-2019. This research was conducted using panel data analysis method using the best approach Fixed Effect Model. This research uses Regency/City objects in Banten Province in 2015-2019. The results of this study concluded that (1) the human development index variable has a positive relationship with the unemployment rate in Banten Province (2) the minimum wage variable has a negative relationship with the unemployment rate in Banten Province (3) the investment variable has a positive relationship with unemployment rate in Banten Province.